Nonlinear Model and Ballistic Impact of Body Aerodynamics for Canard Dual-Spin Aircraft - Xinxin Zhao; Jinguang Shi; Huajie Ren; Zhongyuan Wang (Aerospace, 2025)
Targeting the nonlinear issues of the canard dual-spin aircraft, which relies on the high-speed rotation of the afterbody for flight stability and achieves trajectory correction by adjusting the roll angle of the low-speed rotating forebody to alter aerodynamics, the establishment of an accurate aerodynamic model is crucial for in-depth studies of its ballistic characteristics and design. For this, by taking the effects of canard–body interference, fore/aft body reversal, and other factors into account, an accurate model of the body aerodynamics applicable to large angles of attack is presented. This model theoretically elucidates the intricate relationship between the body aerodynamics and both the flight state and the aerodynamic parameters of the original aircraft. Subsequently, numerical simulations are conducted to analyze the body nonlinear aerodynamic characteristics and their impact on ballistics. The results reveal that all aerodynamic forces and moments acting on the aircraft body, particularly the Magnus force and moment, exhibit strong nonlinearities due to the coupling between the forebody roll angle and the amplitude and phase of the complex angle of attack. Moreover, the established model accurately captures the body aerodynamics and the influence of various disturbance factors, which can significantly alter the controlled angular motions and corrected ballistic calculations.